Membangun Pembelajaran PAI melalui Desain Kompetensi di SMK Negeri 2 Probolinggo - Chici Cahyaningrum; Nafisha Arifa Azahra; Wahyu Musrifah Ramadani; Devy Habibi Muhammad (Al-Kindi, 2026)
Islamic Religious Education (PAI) in vocational high schools (SMK) faces significant challenges in balancing cognitive, affective, and psychomotor aspects to align with workforce needs and character building. This research aims to analyze and describe the application of competency design and the formulation of learning objectives in improving the quality of PAI learning at SMK Negeri 2 Probolinggo. Using a qualitative approach with a case study method, data were collected through participatory observation and in-depth interviews with PAI teachers as key instruments. The results indicate that effective competency design is achieved through systematic steps, including student needs analysis, determining core and basic competencies that integrate spiritual values with 21st-century skills, and developing comprehensive competency-based evaluations. Implementation strategies in the classroom have shifted from teacher-centered to student-centered learning through Contextual Teaching and Learning (CTL), Project-Based Learning (PBL), and differentiated learning approaches. This study concludes that strengthening the pedagogical, linear, and spiritual competencies of teachers is the primary key to forming a moderate "Profil Pelajar Pancasila" that is adaptive to global dynamics.